Ceramics for Electronics and Energy: Issues and Opportunities. Issue 5 (12th August 2013) - Testino, Andrea
<x xml:space="preserve">Abstract</x> The ceramic electronic components market is growing mainly because of portable electronics. The market drives toward device miniaturization, which is achievable by extremely tiny electronic components; but the electronic components miniaturization itself is approaching the technical limit. The R&D efforts of academic and industrial scientists are focused not only on new materials and advanced characterization tools, but also on advanced ceramic processing techniques to shift the miniaturization limit. For instance, the production of submicrometer powders prepared by conventional methods has reached the level where new strategies, such as bottom‐up methods for material synthesis might be required for further improvement. Established ceramic processing technologies are close to limitations too — for example, submicrometer tape‐casted ceramic layers — and the re‐evaluation of methods, which have not yet been used on an industrial level, might be the breakthrough. Solutions may come from disciplines outside of the traditional ceramic‐manufacturing world as well. Advanced analytical tools and deeper understanding of the solid state chemistry have revealed the importance of grain boundaries characteristics and submicrometer scale structures. Nanoscale engineering has become crucial in many fields. Many ceramic components are based on metals with a potential environmental impact (e.g., Pb, Cd, Te) or limited resources (e.g., rare earth elements). A growing scientific activity is devoted to greener formulations, less rare raw materials, and the entire life‐cycle of ceramic components. "Healthcare" and "Energy" are appealing markets. Bio‐integrated electronics based on flexible silicon integrated circuit open opportunities for social benefit — and fruitful business — beyond imagination. Energy market is in need of materials, which can operate at higher temperature and higher energy density with improved reliability. Ceramic materials open new chances.